IT Landmarks in Less-Developed Countries: The Chilean Case - Baeza-Yates, Ricardo A.; Fuller, David A.; Pino, Jose A. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
We present the main landmarks of IT development in Chile. Currently, Chile has one of the healthiest economies and IT levels in Latin America. It may be useful for other less-developed countries to profit from Chile's experience.